2016
DOI: 10.1103/physreva.93.023607
|View full text |Cite
|
Sign up to set email alerts
|

Generation of atom-light entanglement in an optical cavity for quantum enhanced atom interferometry

Abstract: We theoretically investigate the generation of atom-light entanglement via Raman superradiance in an optical cavity, and show how this can be used to enhance the sensitivity of atom interferometry. We model a realistic optical cavity, and show that by careful temporal shaping of the optical local oscillator used to measure the light emitted from the cavity, information in the optical mode can be combined with the signal from the atom interferometer to reduce the quantum noise, and thus increase the sensitivity… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 61 publications
(91 reference statements)
0
15
0
Order By: Relevance
“…seperate statepreparation and interrogation stages), we simply optimised the controllable parameters of the system using the final sensitivity as the appropriate metric. The significant increase in performance that this approach pro-vides indicates the power of this technique, and could be used in other quantum-enhanced sensing protocols that involve the use of a controllable dynamic parameter, such as when coherent coupling pulses are used to increase the entangled population spontaneously generated from spinchanging collisions [41,47,48], four-wave mixing [49], or Raman superradiance [50,51]. Finally, we note that while this scheme is capable of enhancing the sensitivity of atomic clocks and magnetometers, the continuous use of coupling pulses is incompatible with atomic gravimeters and accelerometers due the the requirement of spacetime separated modes [1,52].…”
Section: Discussionmentioning
confidence: 99%
“…seperate statepreparation and interrogation stages), we simply optimised the controllable parameters of the system using the final sensitivity as the appropriate metric. The significant increase in performance that this approach pro-vides indicates the power of this technique, and could be used in other quantum-enhanced sensing protocols that involve the use of a controllable dynamic parameter, such as when coherent coupling pulses are used to increase the entangled population spontaneously generated from spinchanging collisions [41,47,48], four-wave mixing [49], or Raman superradiance [50,51]. Finally, we note that while this scheme is capable of enhancing the sensitivity of atomic clocks and magnetometers, the continuous use of coupling pulses is incompatible with atomic gravimeters and accelerometers due the the requirement of spacetime separated modes [1,52].…”
Section: Discussionmentioning
confidence: 99%
“…More generally, there are likely to be considerably more photons than atoms (n f < 1); since photons are "cheap" compared with atoms (in the sense that there are more severe particle-flux constraints on atoms than photons [48,49]), a large absolute sensitivity could be obtained by increasing the number of pump photons (i.e. increasing N ) while simultaneously decreasing n f (therefore decreasing the per particle sensitivity), in the spirit of information recycling protocols [26,27,[50][51][52][53].…”
mentioning
confidence: 99%
“…It has been shown that in the presence of entanglement between the state and some auxiliary system, the metrological usefulness of the state may be enhanced by allowing measurements on the auxiliary system [42][43][44][45][46][47][48]. However in this paper we take a different approach, and study the metrological usefulness of a state if measurements of the auxiliary system are forbidden.…”
Section: Introductionmentioning
confidence: 98%